Analyzing the Islamist and new-Islamist discourse on minorities in an Islamic state - Bhat, Adil Hussain (Penerbit Universiti Kebangsaan Malaysia, 2023)
The call by the Islamist scholars for an Islamic state governed by the sharia law has given rise to the criticism that Islamic state would involve the discrimination of religious minorities and their reversion to inferior or second-class status. In this paper, the Islamic discourse on non-Muslims living in an Islamic state is examined under two trends: Islamist and the New Islamist trend. This paper is an attempt to highlight and understand the Islamic discourse on the citizenship of non-Muslim minorities. It will also contribute to how this discourse has changed over time. More importantly, it will put forth the efforts made by New-Islamist scholars who associate themselves with wasatiyyah movement to reconcile the Islamist and modern concept ofcitizenship. Notwithstanding, the objectives of this paper is threefold: to discuss the relationship between Muslim majority and non-Muslim minority in a proposed Islamic state; to identify the basic rights such as freedom of religion and other rights, that are available to non-Muslims residents of an Islamic state; and to assess how far the new-Islamist scholars have been successful in reconciling the traditional Islamist discourse with the modern nation-state notion of citizenship.